Routine activity theory and malware, fraud, and spam at the national level - Kigerl, Alex (Crime, law and social change, 2021)
Email spam is one of the primary means to facilitate the perpetration of internet fraud and the distribution of malware. The present research sought to examine the impact of routine activity theory at the national level on three forms of cybercrime perpetrated through email spam. A sample of 871,146 spam email messages sent in 2012 were divided into three categories: fraudulent emails, emails spreading malware, and non-serious spam emails. The measures were then aggregated by country and five measures of routine activity theory at the national level were tested for their impact on cybercrime among 120 nations. Concurrent with prior research, the results indicated that internet users per capita positively predicted all three forms of cybercrime. Unlike previous research, GDP presented a different relationship amongst all three outcomes: positive for spam, negative for fraud, and nonsignificant for malware. Implications of these findings and suggestions for future research are discussed.